1993
DOI: 10.1159/000236488
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the IgE Binding to a Peptide Derived from the House Dust Mite Allergen <i>Der </i><i>p</i> II Indicates that the IgE Response Is Highly Polyclonal

Abstract: The fine specificity of IgE antibody binding to peptide 65-78 of the house dust mite major allergen Der p II was examined by comparison with binding to two peptides in which the cysteines corresponding to cys73 and cys78 in Der p II were substituted by serines and methionines. Differences in binding behavior indicated that at least three different subpopulations of IgE antibodies bound to peptide 65-78. Even at the level of such a small fragment the IgE response in individual donors prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This increase in polyclonality following repeated exposure to the same antigen is a clear indication that downregulation of naive B cells via FcR gamma II is not an absolute effect, since some B cells escape this downregulation. In a highly‐selected model system, the human IgE response was found to be highly polyclonal (94).…”
Section: Is the Ige Response Special In Relation To Cross‐reactivity?mentioning
confidence: 99%
“…This increase in polyclonality following repeated exposure to the same antigen is a clear indication that downregulation of naive B cells via FcR gamma II is not an absolute effect, since some B cells escape this downregulation. In a highly‐selected model system, the human IgE response was found to be highly polyclonal (94).…”
Section: Is the Ige Response Special In Relation To Cross‐reactivity?mentioning
confidence: 99%
“…However, it is very unlikely that the class switch is the only element that controls IgE antibody production. First, IgE antibody responses are polyclonal in the sense that many different B-cell clones are involved, 7,8 implying that IgE switch has occurred repeatedly. Second, the clonal size of IgE-switched B cells is much smaller than that for other antibodies, 9 and IgE-switched B cells are strikingly susceptible to apoptosis induced by cell crowding.…”
Section: The B Cell Between Hygiene and Dangermentioning
confidence: 99%
“…These data suggest that the low level of IgE production is not only due to low frequency of the IgE class switch, but also by a post-switch expansion/differentiation blockade. Upon analysis of the fine-specificity of IgE to a single allergen (the mite allergen Der p 2) it was concluded that the IgE response to this allergen involves many different clones, which would not be expected if the switch itself was the only road block on the way to IgE production [107]. Based on these and other data, Aalberse and Platts-Mills reviewed in 2004 the origin and fate of the IgE switched B cell in relation to the type of antigen [108].…”
Section: Fate Of Ige-switched B Cellsmentioning
confidence: 99%